THE SIMULATION SYSTEM OF TRACTION POWER SUPPLY FOR THE STUDY OF THE ELECTRICAL ENERGY QUALITY TO THE TRACTION SUBSTATIONS OF AC - Bosiy, D. O. (Science and Transport Progress, 2008)
The existing methods of calculation of electromagnetic processes in the systems of traction AC power supply have been analyzed. The modern simulation methods for studying the electromagnetic processes have been proposed. The expression for calculation of current distribution functions by means of matrix algebra has been obtained. The sequence of simulation modeling has been presented.